Severe maternal morbidity during pregnancy, delivery and puerperium in the Netherlands: a nationwide population‐based study of 371 000 pregnancies - Zwart, JJ; Richters, JM; Öry, F; De Vries, JIP; Bloemenkamp, KWM; Van Roosmalen, J (BJOG : an international journal of obstetrics and gynaecology, 2008)
Objective  To assess incidence, case fatality rate, risk factors and substandard care in severe maternal morbidity in the Netherlands. Design  Prospective population‐based cohort study. Setting  All 98 maternity units in the Netherlands. Population  All pregnant women in the Netherlands. Methods  Cases of severe maternal morbidity were collected during a 2‐year period. All pregnant women in the Netherlands in the same period acted as reference cohort (n = 371 021). As immigrant women are disproportionately represented in Dutch maternal mortality statistics, special attention was paid to the ethnic background. In a subset of 2.5% of women, substandard care was assessed through clinical audit. Main outcome measures  Incidence, case fatality rates, possible risk factors and substandard care. Results  Severe maternal morbidity was reported in 2552 women, giving an overall incidence of 7.1 per 1000 deliveries. Intensive care unit admission was reported in 847 women (incidence 2.4 per 1000), uterine rupture in 218 women (incidence 6.1/10 000), eclampsia in 222 women (incidence 6.2/10 000) and major obstetric haemorrhage in 1606 women (incidence 4.5 per 1000). Non‐Western immigrant women had a 1.3‐fold increased risk of severe maternal morbidity (95% CI 1.2–1.5) when compared with Western women. Overall case fatality rate was 1 in 53. Substandard care was found in 39 of a subset of 63 women (62%) through clinical audit. Conclusions  Severe maternal morbidity complicates at least 0.71% of all pregnancies in the Netherlands, immigrant women experiencing an increased risk. Since substandard care was found in the majority of assessed cases, reduction of severe maternal morbidity seems a mandatory challenge.